Evaluating LEADER program support for local projects: insights from the Czech Republic and Hungary (2007–2013) - Adél Veselicz; Ondřej Konečný; János Pénzes; Csaba Patkós (Cogent Social Sciences, 2025)
The rural areas of the European Union are very multidimensiona, they have different social and economic problems. The LEADER programme tries to reflect on these issues and help rural areas by giving locals the ability to develop their environment according to their needs. Local action groups (LAGs) are responsible for the distribution of funds. In the course of our research activity, we wanted to compare the distribution of resources of the Czech and Hungarian LEADER LAGs in the 2007–2013 period. We collected data from LEADER LAGs, such as the amount of LEADER funds allocated to settlements, the unemployment rate of each LAGs, per capita income, population density and the number of member settlements. Using the Gini-index, we calculated the resource distribution inequality of the LAGs and then correlation calculations were performed using the Gini-index and the other socio-economic indicators. With the aim of discovering whether the examined indicators have an effect on the distribution of resources within the LAGs. Our study shows no stronk link between the investigated indicators and the LEADER fund distribution. We concluded that, the distribution of LEADER funds among settlements can be influenced by other socio-economic factors.